A sustained high-temperature fusion plasma regime facilitated by fast ions - Han, H.; Park, S. J.; Sung, C.; Kang, J.; Lee, Y. H.; Chung, J.; Hahm, T. S.; Kim, B.; Park, J.-K.; Bak, J. G.; Cha, M. S.; Choi, G. J.; et al. (Nature (London), 2022)
Nuclear fusion is one of the most attractive alternatives to carbon-dependent energy sources 1 . Harnessing energy from nuclear fusion in a large reactor scale, however, still presents many scientific challenges despite the many years of research and steady advances in magnetic confinement approaches. State-of-the-art magnetic fusion devices cannot yet achieve a sustainable fusion performance, which requires a high temperature above 100 million kelvin and sufficient control of instabilities to ensure steady-state operation on the order of tens of seconds 2 , 3 . Here we report experiments at the Korea Superconducting Tokamak Advanced Research 4 device producing a plasma fusion regime that satisfies most of the above requirements: thanks to abundant fast ions stabilizing the core plasma turbulence, we generate plasmas at a temperature of 100 million kelvin lasting up to 20 seconds without plasma edge instabilities or impurity accumulation. A low plasma density combined with a moderate input power for operation is key to establishing this regime by preserving a high fraction of fast ions. This regime is rarely subject to disruption and can be sustained reliably even without a sophisticated control, and thus represents a promising path towards commercial fusion reactors. A magnetic confinement regime established at the Korea Superconducting Tokamak Advanced Research device enables the generation of plasmas over 10 8 kelvin for 20 seconds with the aid of fast ions without plasma edge instabilities or impurity accumulation.